The Quality of Catholic Education in a Diocesan School Relative to the Philippine Catholic School Standards - Joel M. Bual; Dennis Madrigal (Philippine Social Science Journal, 2018)
Evangelization is the primary purpose of Catholic education. However, due to the depreciation of moral values brought about by secularism and globalization, the identity and mission of Catholic schools are compromised. Thus, this paper primarily intended to assess the level of quality of Catholic education in a Diocesan School in accordance with the five domains of the Philippine Catholic Schools Standards (PCSS). A quantitative study was used through a standardized survey questionnaire to gather data from 337 respondents―administrators, teachers, non-teaching personnel, students, and parents of the school. Using descriptive and inferential data analyses, the results revealed that the Diocesan school adheres to the quality standards for Catholic education but needs to continuously improve to meet the highest possible standards. Of the five (5) domains, the learning environment was rated high by respondents while leadership and governance ranked low. Moreover, the study showed that parents have significantly higher assessment compared to other respondents in terms of assessing the quality Catholic education of the institute. The findings further affirmed the important role that administrators play in the effective management of schools to achieve quality Catholic education and to ensure operational vitality in responding to its evangelical mission. Hence, the active involvement of the members of the school community to this effect.